Ferrate(VI) pretreatment before disinfection: An effective approach to controlling unsaturated and aromatic halo-disinfection byproducts in chlorinated and chloraminated drinking waters - Jiaqi Liu; Henry Lujan; Birendra Dhungana; William C. Hockaday; Christie M. Sayes; George P. Cobb; Virender K. Sharma (Environment International, 2020)
Disinfection is an essential process of drinking water treatment to eliminate harmful pathogens, but it generates potentially toxic disinfection byproducts (DBPs). Ferrate (FeO42-, Fe(VI)) was used to pre-oxidize natural organic matter (NOM, the precursor of DBPs) in source water to control DBP formation in subsequent chlorine or chloramine disinfection. Currently, it is unclear how Fe(VI) changes the structure of NOM, and no information details the effect of Fe(VI) pretreatment on the aromatic DBPs or the speciation of overall DBPs generated in subsequent disinfection of drinking water. In the present paper, Fe(VI) was applied to pretreat simulated source water samples at a Fe(VI) to dissolved organic carbon mole ratio of 1:1 at pH 8.0. 13C nuclear magnetic resonance spectroscopy was newly employed to characterize NOM in simulated source waters with and without Fe(VI) treatment, and it was demonstrated that Fe(VI) converted unsaturated aromatic C functional groups in NOM to saturated aliphatic ones. High-resolution mass spectrometry (HRMS) and high performance liquid chromatography/triple quadrupole MS were applied to analyze the DBPs generated in chlorination and chloramination of the source waters with and without Fe(VI) pretreatment. It was confirmed that Fe(VI) pretreatment followed by chlorination (or chloramination), generated DBPs containing less unsaturated, halogenated, and aromatic moieties than chlorination (or chloramination) without pretreatment by Fe(VI). Finally, the cytotoxicity of disinfected drinking water samples were assessed with the human epithelial colorectal adenocarcinoma Caco-2 cell line (a model of the intestinal barrier for ingested toxicants), and the results show that Fe(VI) pretreatment detoxified the chlorinated and chloraminated drinking waters. Keywords: Ferrate, Disinfection byproduct, Chlorination, Chloramination, Toxicity